PEMBERDAYAAN PERAN IBU DALAM PAUD INFORMAL BERBASIS KELUARGA MELALUI PENDAMPINGAN AKTIVITAS IBU DAN ANAK DI RUMAH DENGAN METODE BERMAIN PERAN - Lilis Suryani (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2008)
Informal early child education has not been well developed and there are many mothers who do not understand how to educate a child properly, suitable for the child development and characteristics. Educating the child in the family is rarely done by mother and it becomes more difficult when it has to face mother’s domestic daily routine activities which consume a lot of time. This article puts forward a number of reasons why early child education is neglected in the family and purposes how a mother should educate a child properly.